22‐4: Invited Paper: OLEDs for Wearables: From Form Factor Engineering to Healthcare Applications. Issue 1 (28th June 2021) - Yoo, Seunghyup; Kim, Taehyun; Lee, Hyeonwoo; Moon, Hanul; Kim, Eungjun; Lee, Seunghee
Abstract : OLEDs have been established as key light sources for high‐end displays. In addition to their ideal optical characteristics, the inherent compatibility with various form factors gives OLEDs a competitive edge with respect to conventional technologies. Such versatility in form factors makes OLEDs attractive not only for displays but also for wearable devices. In this respect, this talk explores OLEDs from the perspectives of wearable applications. The first part describes engineering required for highly flexible and stretchable OLEDs adopting non‐conventional electrodes. The second part then introduces OLEDs used in wearable healthcare applications such as pulse oximetry sensors.